1993
DOI: 10.1152/ajpheart.1993.264.4.h1093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atrial fibrillation on left and right atrial dimensions, pressures, and compliances

Abstract: The effects of atrial fibrillation on left and right atrial dimensions, pressures, and compliances were examined in two groups of seven barbiturate-anesthetized open-chest pigs. Atrial diameters and pressures were recorded during atrioventricular (AV) pace and thereafter during atrial fibrillation. Both rhythms were studied with constant ventricular rate after complete AV block. Left atrial maximal diameter, which appeared at the end of the atrial filling phase, decreased from 32.4 (28.9-36.7; median and 95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…20 When it comes to the effects of AF on right atrial compliance in animal models, the increased pressure and decreased compliance of the right atrium have been demonstrated during AF. 21,22 Taken together with the current findings of impaired RV function, we can speculate that the association of AF with RV dysfunction indicates that AF may not simply be a risk factor for stroke but also a mediator for LV or RV HF. Thus, given the observance of a significant difference in tricuspid s 0 and e 0 in the patients who experienced events, it may be that decreased RV contraction and relaxation would be accompanied by decreased RV compliance.…”
Section: Rv Dtisupporting
confidence: 66%
“…20 When it comes to the effects of AF on right atrial compliance in animal models, the increased pressure and decreased compliance of the right atrium have been demonstrated during AF. 21,22 Taken together with the current findings of impaired RV function, we can speculate that the association of AF with RV dysfunction indicates that AF may not simply be a risk factor for stroke but also a mediator for LV or RV HF. Thus, given the observance of a significant difference in tricuspid s 0 and e 0 in the patients who experienced events, it may be that decreased RV contraction and relaxation would be accompanied by decreased RV compliance.…”
Section: Rv Dtisupporting
confidence: 66%
“…However, in these studies, the impact of AF on LAA functions of the patients with severe mitral regurgitation has not been investigated. The previous study have identified that AF impaired LAA functions definitely, in patients with severe mitral regurgitation and this was thought to be due to systolic dysfunction of LAA, following the loss of active atrial contraction [23,24]. During atrial fibrillation, synchronized atrial contraction is lost and cardiac output declines.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, atrial pressure increases [23]. Furthermore, instanta- neous diastolic atrial compliance is decreased in both right and left atrium, after induction of atrial fibrillation [24]. It has been revealed that, the methods, used to evaluate the left atrial appendage functions are affected by the loading conditions [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…reported that the stiffness index calculated as mean LAP/ peak atrial longitudinal strain is an independent predictor for LA stiffness . Alternatively, LA compliance can be calculated as the ratio of the change in LA volume to the change in LAP based on other studies . Fourth, this study focused on a selected group of patients in order to exclude structural and hemodynamic factors as much as possible.…”
Section: Discussionmentioning
confidence: 99%